Development of a Versatile Protein Labeling Tool for Live‐Cell Imaging Using Fluorescent β‐Lactamase Inhibitors. (27th March 2023) - Minoshima, Masafumi; Umeno, Taro; Kadooka, Kohei; Roux, Margaux; Yamada, Namiko; Kikuchi, Kazuya
Abstract: To understand the function of protein in live cells, real‐time monitoring of protein dynamics and sensing of their surrounding environment are important methods. Fluorescent labeling tools are thus needed that possess fast labeling kinetics, high efficiency, and long‐term stability. We developed a versatile chemical protein‐labeling tool based on fluorophore‐conjugated diazabicyclooctane β‐lactamase inhibitors (BLIs) and wild‐type TEM‐1 β‐lactamase protein tag. The fluorescent probes efficiently formed a stable carbamoylated complex with β‐lactamase, and the labeled proteins were visualized over a long period of time in live cells. Moreover, use of an α‐fluorinated carboxylate ester‐based BLI prodrug enabled the probe to permeate cell membranes and stably label intracellular proteins after unexpected spontaneous ester hydrolysis. Lastly, combining the labeling tool with a pH‐activatable fluorescent probe allowed visual monitoring of lysosomal protein translocation during autophagy. Abstract : A versatile protein labeling system was developed using non‐β‐lactam β‐lactamase inhibitors. Fluorophore‐diazabicyclooctane prodrug conjugates efficiently and stably labeled β‐lactamase tag‐fused proteins localized in various intracellular compartments in living cells. Furthermore, use of a pH‐activatable fluorophore allowed visualization of lysosomal protein trafficking at the late stage of autophagy under cellular starvation.